Analysis of Factors Influencing Revisit Intention Among Guests at Oakwood Hotel & Residence Surabaya - Theodorus, Lyvia Sita (SABA: Journal of Tourism Research, 2024)
This study aims to analyse the factors influencing guests' revisit intentions at Oakwood Hotel Residence Surabaya, while also developing strategies to enhance the hotel's competitiveness in the hospitality industry. Recognizing the critical role of guest satisfaction in fostering loyalty, this research investigates the underlying reasons for the low rate of return visits. A qualitative research approach was employed, with data collected through observations and interviews with seven informants, comprising both staff and guests. The findings identified four key factors influencing revisit intentions: location, facilities, service quality, and promotions. A SWOT analysis was conducted to formulate strategic recommendations, including offering attractive packages at competitive prices, enhancing human resource quality, and increasing brand awareness. These insights are expected to assist hotel management in crafting strategies to boost guest loyalty and strengthen competitiveness in Surabaya's hospitality sector.